The Communicative Functions of Spatial Arts in the Art History of the Late 19th — First Half of the 20th Centuries - Limanskaya, Liudmila Yu. (Actual Problems of Theory and History of Art, 2018)
This article focuses on the correlation between the Theory of Evolution and psychoanalysis which influenced the methodology of art history researches at the end of the 19th — first half of the 20th centuries.The author takes into consideration the verbal nature of the communicative function of spatial arts which is based on the phenomenon of empathy — the natural human ability to imitate the nature and to make it emotionally expressive. Thus, the article shows the impact of Empathy on “Kinesics” (Latin) — the plastic expressiveness of the body, which is widely used in the Fine Arts.Here it can be also seen the theoretical and methodological interrelation between the row of theories, such as: the Evolutionary Theory of Charles Darwin, the theory of aesthetic tmpathy of R. Fisher, H. Wölfflin’s aesthetics of pure visual, the psychoanalysis of S. Freud, the theory of archetypes by C. G. Jung, the theory of “pathos formula” by A. Warburg, the theory of symbolic forms by E. Kassirer, the iconography of E. Panofsky, and, finally, the connection between the Neo-evolutionary theory of K. Lorenz and the Perceptionality of E. Gombrich.This research led the author to the following conclusion: the application of evolutionary theories and psychoanalysis to the study of the history of arts makes it possible to reveal the preverbal basis of the language of plastic arts, gives an opportunity to study the communicative function of the plastic expressiveness of the figurative language of facial expressiveness, movements and gestures in works of fine arts. Furthermore, it enables us to trace the role of “Kinesics” in the formation of artistic symbolism and its place in the process of the historical genesis of cultural and historical memory.
Keywords: empathy; kinesics; evolutionism; psychoanalysis; art history; spatial arts